The new equation is f(x) = (x+2)² + 1
Step-by-step explanation
• If f(x) shifts up m units, then the new formula of the function = f(x) + m
,
• If f(x) shift down n units, then the new formula of the function = f(x) - n
,
• If f(x) shifts right P - units, then the new formula of the function = f(x-p)
,
• If f(x) shifts left q units, then the new formula of the function = f(x+q)
From the given function, first, f(x) = x² is shifted up 1 unit
⇒ f(x) = x² + 1
Then, shifted to the left 2 units.
⇒ f(x) = (x+2)² + 1
Hence, the new equation is f(x) = (x+2)² + 1